(untitled) (Balneo and PRM Research Journal, 2021)
Introduction. Management of patients with chronic pathology requires development of long-term programs with organic combinations of medicamental and non-medicamental influences. Haloaerosoltherapy is a group inhalation of rock salt aerosol with concentration of more than 2-3mg/m3 and certain dispersion (with presence of large-, medium- and small-grained aerosol) aboveground. Material and method. On the basis of literature data review and results of own researches a comprehensive description of haloaerosoltherapy, its mechanisms, available technologies, indications and effectiveness at pulmonary pathology was given. Results and discussion. Basis of haloaerosol curative influence is hyperosmolar stimulus that improves drainage function of bronchi and provides sanitizing effect, which causes further changes at local and systemic levels. This justifies haloaerosoltherapy usage as method of rehabilitation treatment. Comparison of haloaerosoltherapy and other methods of halotherapy (use of halite), in particular, "salt rooms (caves)" was made. It has been proven that "salt rooms" can be used only as spa procedure. Conclusions. Application of term "halotherapy" to all methods that use halite or underground treatment is incorrect. This determines necessity for stop using this term. It is necessary to differentiate clearly applied methods of treatment using terms that reflect the essence of therapeutic effect. Haloaerosoltherapy should be considered a method of respiratory rehabilitation with a proven mechanism of action and effectiveness. Haloaerosol is obtained using specific devices - halogenegenerators. The effectiveness of haloaerosoltherapy immediately after the course of treatment and in remote period is testified.